PENGARUH PERBANDINGAN SARI BUAH NANAS DENGAN SARI WORTEL SELAMA PENYIMPANAN TERHADAP MUTU FRUIT TEA - Baya Mawar Berutu (Jurnal Rekayasa Pangan dan Pertanian, 2019)
This study was performed to determine the best ratio of pineapple juice and carrot juice to produce qualified and nutritious fruit flavored tea drinks (Fruit Tea) and prefered by people. Method of this study was  randomized block design with two factors i.e. the ratio of pineapple juice with carrot juice (S): (100%:0%), (75%:25%), (50%:50%), (25%:75%) and (0%:100%) and storage time (L) : (0 day), (5 days), (10 days), and (15 days). The results showed that the effect of ratio of pineapple juice and carrot juice  had  highly significant effect on total soluble solid, pH, vitamin C, total acid, total microbes and organoleptic value of taste. Storage time had highly significant effect on pH, vitamin C, total acid,  total microbes and organoleptic value of taste. The interaction of the two factors had highly significant effect on total microbes. The best composition which gave the best effect on Fruit Tea was ratio of pineapple juice and carrot juice of (75%:25%) and 5 days of storage.